Pendampingan Penerapan Teknologi Self Watering System Untuk Budidaya Tanaman Hias Indoor Bagi Petani Tanaman Hias di Kota Medan - Diningrat, Diky Setya; Sibuea, Abdul Muin; Asmin, Asmin; Harahap, Novita Sari; Sari, Ayu Nirmala (Jurnal Pengabdian Masyarakat Pinang Masak, 2024)
The purpose of this Community Partnership Program (PKM) activity is to help partners, namely start-ups engaged in the downstream of biotechnology products, namely PT. G10 Agrotech in solving the problems it faces, namely the problem of stagnant marketing of ornamental plants produced by the G10 laboratory. To develop this business, partners want to be assisted in technology that can overcome the stagnant marketing of ornamental plants, and product standardization to expand the market that has been built so far, so that they can gain more trust from consumers and be further developed into superior products from this start-up. Self-watering system technology is believed to be the solution to the problems partners face. This technology allows ornamental plants to be grown indoors, where people no longer have adequate land and yard. This technology is a solution to increase sales turnover so that this business develops and creates jobs. The method used to achieve the objectives of this PKM activity is the method of education and training in the transfer of self-watering system technology and assistance in the production of tools and materials for developing self-watering systems. PKM activity carried out include; Providing direct education and training from related parties, and providing assistance in the production of tools and materials for the development of self-watering systems. It is hoped that this PKM program will produce superior standardized products that can compete globally.